2017
DOI: 10.1590/0001-3765201720160554
|View full text |Cite
|
Sign up to set email alerts
|

Parasite infracommunities of Leporinus friderici: A comparison of three tributaries of the Jurumirim Reservoir in southeastern Brazil

Abstract: The degradation and homogenization of natural habitats is considered a major cause of biotic homogenization. Many studies have been undertaken on the effects of dams on aquatic wildlife, in particular fish assemblages. But how do dams affect the parasitic fauna of such fish? The aim of the present study was to examine parasitic similarity, comparing the diversity and structure of parasite communities of Leporinus friderici (Characiformes, Anostomidae) in three upstream tributaries under the influence of the Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(28 reference statements)
2
8
0
1
Order By: Relevance
“…Several factors determine differences in the structure of parasite communities of hosts from different populations and localities (Oliveira et al 2017;Yamada et al 2017). The Table 1 Prevalence (P), mean abundance (MA) ± 1 standard deviation (SD), values of odds ratio (OR), confidence interval (CI) with 95% of confidence and p of the respective logistic and Poisson regression associated to the metazoan parasites of Pimelodus blochii (n = 160), from River Acre (n = 80) and River Iaco (n = 80), State of Acre, western Brazilian Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors determine differences in the structure of parasite communities of hosts from different populations and localities (Oliveira et al 2017;Yamada et al 2017). The Table 1 Prevalence (P), mean abundance (MA) ± 1 standard deviation (SD), values of odds ratio (OR), confidence interval (CI) with 95% of confidence and p of the respective logistic and Poisson regression associated to the metazoan parasites of Pimelodus blochii (n = 160), from River Acre (n = 80) and River Iaco (n = 80), State of Acre, western Brazilian Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…As larvas de digenéticos (metacercárias) foram encontradas em diversos órgãos do peixe, por apresentar baixa especificidade e rápida adaptação ao ambiente (TAKEMOTO et al, 2009). Esse parasito já foi descrito L. friderici de várias regiões do Brasil (TRAVASSOS et al, 1928;GUIDELLI et al, 2006;TAKEMOTO et al, 2009;YAMADA et al, 2017), inclusive em rios do estado do Amapá (OLIVEIRA et al, 2016). (PAVANELLI et al, 1998).…”
Section: Resultsunclassified
“…The life stage of each parasite will generally have its own direct and indirect responses to a stressor, as the impact becomes more evident as life cycle complexity increases (Lafferty & Kuris, 1999). Moreover, some studies in recent years have observed that the local extinction of parasite species, changes in prevalence, diversity, composition and dominance of parasitic infra-communities, an increase of monoxenous parasites (monogenetic, protozoa and crustaceans), and reduction of heteroxenous parasites (digenetic, nematodes and acanthocephalans) due to biotic and abiotic changes in the ecosystem (Karling et al, 2013;Yamada et al, 2017). We found that, over the years, the composition of the parasitic fauna of P. lineatus changed, and the dominant species was different in the two periods.…”
Section: Discussionmentioning
confidence: 99%